Branding UMKM Desa Ngadiboyo Melalui Logo Baru - Hendra Maulana; Davina Azalia Erson; Wilda Cahyani Sukma; Narendra Pasha Maulana; Girycki Sana Aleffin; Yurisa Wianuari (Institut Nalanda, 2023)
MSME (micro, small, and medium enterprises) branding is one the most crucial aspects to a business operation. Branding can help improve the sales number by increasing brand awareness among the public. This research is conducted in the village of Ngadiboyo, Rejoso sub-district, Nganjuk regency. The main purpose of this research is to provide elucidation to the local MSMEs owner regarding logo branding that would play an important role of increasing their sales figures and as a marketing tool towards their potential customers. This is a descriptive research to explain each stage conducted by the researcher in a detailed manner. This research was conducted in order to have an affective and cognitive impact. This is effective in providing an understanding of logo branding to MSME actors. This research is expected to be able to make MSME owners realize the importance of logo branding in business development.